Talkpod Program Broadcasting Diversification Program on Net Tv Through Digital Platform - Raudhatul Fitri; Rustim; Dynia Fitri; FX. Yatno Karyadi (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This research is to reveal that broadcasting diversification is an important strategy for television stations in facing the development of broadcasting technology platforms and changes in social media consumption patterns of android-based communities. The "Talkpod" program is one of NET TV's innovations that combines the concepts of talk shows and podcasts, which are then distributed through digital platforms. The research method used is a qualitative method and data collection techniques by conducting interviews, observations, and document studies. This research approach focuses on television program broadcasting strategies in expanding audience reach.The results show that the diversification of broadcasting the "Talkpod" program through digital platforms provides several strategic advantages for Net Tv. First, expanding audience reach, especially among millennials and Gen Z who are more active on digital platforms. Second, increasing interaction and engagement with the audience through interactive features offered by digital platforms. Third, opening up new opportunities for monetization through digital advertising and collaboration with various brands.